RU_CAGeochem, a database and sample repository for Central American volcanic rocks at Rutgers University. (11th February 2014) - Carr, Michael J.; Feigenson, Mark D.; Bolge, Louise L.; Walker, James A.; Gazel, Esteban
<x xml:space="preserve">Abstract</x> The Rutgers University Central American geochemical dataset focuses on the active volcanoes related to the Cocos‐Caribbean convergent plate boundary that extends from Guatemala to Costa Rica in Central America. The RU prefix signifies that the data and samples are primarily from the long‐term Central American research project started at Dartmouth College in 1970 and continued at Rutgers University from 1974 to the present. The database is decidedly uneven because of the impressive improvement of analytical techniques over the span of data collection. Further complications arose because most of the sampling and analysis were part of the educational process for many different undergraduate and graduate students using different types of instruments. This note presents, as a reasonably coherent whole, geochemical data and metadata for about 1400 samples collected by at least 40 students and colleagues. Many unpublished Sr, Nd, and Pb isotopic ratios are included here but most of the new data are metadata that provide greatly improved descriptions of the tectonic settings, locations, and status of the samples as well as estimates of data quality.